Ventricular fibrillation caused by massive right coronary air embolism: a case report - Hongcai Zhang; Ai-ling Huang; Qian Nie; Haseeb Sattar; Xie Wen (The Egyptian Heart Journal)
Abstract Background Coronary air embolism is a rare but severe complication of coronary interventions. Case presentation We present a case of a massive air embolism in the right coronary artery during percutaneous coronary intervention, resulting in ventricular fibrillation. The patient was successfully resuscitated with electric defibrillation, leading to full recovery and TIMI 3 coronary flow. The final fractional flow reserve showed no residual coronary microvascular dysfunction. Conclusion Our finding suggests that inducing strong myocardial contractions with a cardioverter defibrillator may effectively disperse large air emboli and restore coronary circulation.